1999
DOI: 10.1292/jvms.61.979
|View full text |Cite
|
Sign up to set email alerts
|

Lack of LH Response to Exogenous Estradiol in Heifers with ACTH-Induced Ovarian Follicular Cysts.

Abstract: ABSTRACT. The aim of the present study was to examine the LH response to exogenous estradiol in 4 heifers with ACTH-induced ovarian follicular cysts. During the control experiment, administration of estradiol 24 hr after PGF 2α in luteal phase heifers resulted in a LH response in all 4 heifers. The LH response was obtained between 16-20 hr after estradiol administration. The peak LH concentration (Mean ± SEM; 5.1 ± 0.8 ng/ml) during the control study was significantly different (P<0.05) from the concentration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2001
2001
2006
2006

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…8). Our results [11,12,22] and those of many other studies [7,8,[13][14][15][16][17][18] suggest that the key physiological change in cystic cows is an abnormality in LH secretion. Under normal conditions, a sufficient amount of estradiol induces an LH surge and the dominant follicle ovulates.…”
Section: Model For Mechanism Of Development Of Follicular Cystssupporting
confidence: 82%
See 1 more Smart Citation
“…8). Our results [11,12,22] and those of many other studies [7,8,[13][14][15][16][17][18] suggest that the key physiological change in cystic cows is an abnormality in LH secretion. Under normal conditions, a sufficient amount of estradiol induces an LH surge and the dominant follicle ovulates.…”
Section: Model For Mechanism Of Development Of Follicular Cystssupporting
confidence: 82%
“…Exogenous injection of estradiol often fails to induce an LH surge in cows with naturally occurring or induced follicular cysts [14][15][16][17][18], whereas injection of GnRH can induce the release of LH [19][20][21]. Taken together, these findings strongly suggest that an important physiological change in cystic cows is the lack of an LH surge owing to a functional abnormality in the estradiolfeedback regulation of LH secretion.…”
Section: Induction Of Follicular Cyst Formation By Perturbation Of Esmentioning
confidence: 95%
“…About 50% of cows became anovular following these treatments (Cook et al 1990, Hamilton et al 1995, Calder et al 1999. Cows with induced follicular cysts appear to be in a physiological state in which high circulating E 2 either produces a delayed GnRH/LH surge (Zaied et al 1981) or does not cause a GnRH/LH surge (Dobson & Alam 1987, Refsal et al 1987, Ribadu et al 1999 due to altered hypothalamic responsiveness to E 2 . However, this is the first study, to our knowledge, that has shown that this lack of hypothalamic responsiveness to E 2 and follicular cysts can be induced by the normal increase in E 2 simply by preventing the post-ovulatory rise in circulating P 4 .…”
Section: Discussionmentioning
confidence: 99%
“…Many cattle had cystic follicular structure observed from 15-45 days after parturition, and follicular cysts as a reproductive disease were mainly diagnosed at 1 to 4 months after parturition. As for the cause of follicular cysts, it was considered that the hypothalamus and pituitary gland were not able to respond to high concentrations of blood estradiol-17β (E 2 ) for induction of estrous events including preovulatory GnRH-LH surge secretion [16,22]. It was thought that a factors in the induction of these reproductive disorders are to feed a large amount of concentrate for milk production and/or much stress applied to the body by milking, housing and feeding systems in high yield dairy cattle [4,8,22].…”
mentioning
confidence: 99%